2008
DOI: 10.1002/dvdy.21776
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression of voltage‐gated calcium channel β subunits in Zebrafish

Abstract: Voltage-gated calcium channels (VGCC) play important roles in electrically excitable cells and embryonic development. The VGCC ␤ subunits are essential for membrane localization of the channel and exert modulatory effects on channel functions. In mammals, the VGCC ␤ subunit gene family contains four members. In zebrafish, there appear to be seven VGCC ␤ subunits including the previously identified ␤1 subunit. cDNAs for six additional VGCC ␤ subunit homologs were identified in zebrafish, their chromosomal locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 42 publications
2
22
0
2
Order By: Relevance
“…Our assignment of zebrafish b4 was based on published expression patterns in zebrafish larvae. Seven genes have been identified in the zebrafish genome encoding voltage-dependent calcium channel b-subunits with distinct expression patterns during development (21). We chose to express b4 together with other calcium channel subunits in this study because it has been shown to express in spinal cord in a segmental fashion, consistent with the location of primary motor neurons.…”
Section: Discussionmentioning
confidence: 98%
“…Our assignment of zebrafish b4 was based on published expression patterns in zebrafish larvae. Seven genes have been identified in the zebrafish genome encoding voltage-dependent calcium channel b-subunits with distinct expression patterns during development (21). We chose to express b4 together with other calcium channel subunits in this study because it has been shown to express in spinal cord in a segmental fashion, consistent with the location of primary motor neurons.…”
Section: Discussionmentioning
confidence: 98%
“…Another possible VGCC-independent function for β 4 is demonstrated by a recent study in zebrafish (135), which express all four subtypes of Ca v βs (506). Morpholino knockdown of zebrafish β 4 abolishes or retards epiboly, an early development process, due to disturbances in mitotic and postmitotic cytoskeletal rearrangements.…”
Section: Ca2+ Channel-independent Functions Of Cavβmentioning
confidence: 89%
“…Since the publication of the Ca v β structures, some investigators have been continuing to perform or interpret experiments based on the notion that the BID interacts with Ca v α 1 (85, 281,302, 388, 441, 506), so before leaving this section, we briefly revisit the BID. The crystal structures show that the BID spans three different regions of Ca v β (SH3, HOOK and GK) and that most of it is completely buried (Fig.…”
Section: Structure Of Cavβmentioning
confidence: 99%
“…Teleost fish, such as Danio rerio , have undergone an additional cycle of whole-genome duplication compared with other vertebrates and hence often possess gene duplicates, termed ohnologues, that resulted from this expansion [47], [48]. For example, several Ca V β subunits (Ca V β2, Ca V β3, and Ca V β4) are both duplicated and expressed in zebrafish [49]. The absence of apparent RGK protein ohnologues in Danio rerio led us to speculate that high RGK protein gene dosages were not tolerated and thus duplicates heavily selected against.…”
Section: Discussionmentioning
confidence: 99%